Transmission electron microscopy characterization of nanomaterials - Kumar, Challa S.S.R (Springer Berlin Heidelberg, 2014)
Third volume of a 40volume series on nanoscience and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about Transmission electron microscopy characterization of nanomaterials. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.